Complications encountered during Forsus Fatigue Resistant Device therapy - Sherif A. Elkordy; Mona M. Salah Fayed; Khaled H. Attia; Amr M. Abouelezz (Dental Press Editora, 2020)
ABSTRACT Introduction: Fixed functional appliances are non-compliant solutions to Class II malocclusion treatment. The clinician, however, should be careful of unexpected complications during the therapy. Methods: 58 female adolescents who presented with Class II malocclusion due to deficient mandible were treated with Forsus Fatigue Resistant Device (FFRD) therapy until an overcorrection to an edge to edge incisor relationship was achieved. Results: Incisor relationship and overjet were corrected successfully in all the subjects. Twenty-two patients had a complications-free treatment, while several complications were encountered with the remaining 36 subjects. In particular, mandibular canine rotation and development of posterior crossbites were the most common complications, with percentages of 51.7% and 25.9% respectively. Other complications included the breakage and shearing of the extraoral tubes of the first molar bands, and excessive intrusion of the upper first molars. Conclusions: FFRD is an efficient appliance for treatment of Class II malocclusion; however, different complications were encountered during the appliance therapy. A focus on taking precautions and applying preventive measures can help to avoid such problems, reducing the number of emergency appointments and enhancing the treatment experience with the appliance.